Progenitor cell mobilization after exercise is related to systemic levels of G‐CSF and muscle damage. Issue 3 (28th September 2014) - Krüger, K.; Pilat, C.; Schild, M.; Lindner, N.; Frech, T.; Muders, K.; Mooren, F. C.
<x xml:space="preserve">Abstract</x> Different types of exercise are characterized by the ability to induce specific physiological stimuli that might be able to induce the mobilization of progenitor cells. The aim of the current study was to investigate the mobilization of hematopoietic progenitor cells (HPCs) and endothelial progenitor cells (EPCs) in response to endurance, resistance, and eccentric endurance exercise and their relation to markers of muscle damage and inflammation. Healthy male subjects performed acute bouts of either endurance exercise, resistance exercise, or eccentric endurance exercise. Numbers of progenitor cells and several markers of muscle damage and inflammation were determined. Although the endurance exercise was followed by an immediate and short increase of both HPCs and EPCs, the eccentric exercise evoked a long lasting increase up to 24 h for HPCs and 48 h for EPCs (P < 0.05). After resistance exercise, an increase of HPCs was only found 3 h after exercise (P < 0.05). A correlation was found between mobilized progenitor cells and systemic levels of granulocyte colony‐stimulating factor (G‐CSF) levels (r = 0.54 and r = 0.51, P < 0.05) as well as for HPCs and creatine kinase levels (r = 0.57, P < 0.05). These results suggest that mobilization of progenitor cells is related to the type of exercise and possibly mediated by G‐CSF and muscle damage.